Determining the structures of halogenated marine natural products by total synthesis - Dyson, BS (2011)
Elatenyne, a brominated C15 acetogenin isolated from the red Laurencia elata marine algae, was originally assigned a pyranopyran structure. Previous total synthesis of the pyranopyran structure has found this assignment to be incorrect. During this work the revised 2,2’-bifuranyl skeleton of elatenyne was suggested, but this skeleton has 32 possible diastereomers. The most likely diastereomer of elatenyne was predicted using computational 13C NMR chemical shift calculation in combination with the possible stereochemical outcomes from the proposed biosynthesis. Chapter 1 introduces the structural misassignment of natural products and describes the misassignment of elatenyne as well as a related chloro enyne. The use of computational methods and biosynthetic postulates to aid structure elucidation are also discussed. Chapter 2 describes the first generation synthesis of cross metathesis coupling partners required for the synthesis of elatenyne from D-mannitol. Chapter 3 describes the completed total synthesis of elatenyne, along with three derivatives and the (E)-isomer of elatenyne; itself a natural product. A comparison of the synthetic data with the isolation data for the natural products is presented, as well as comparison with the synthetic material of Kim and co-workers whose concurrent biomimetic total synthesis is also presented. Chapter 4 describes the modular nature of the devised synthetic route to access any diastereomer of elatenyne and its application to related 2,2’-bifuranyl natural products.